Nanomolar concentrations of the photodynamic compound TLD-1433 effectively inactivate numerous human pathogenic viruses - Kevin M. Coombs; Kathleen K.M. Glover; Raquel Russell; Pavel Kaspler; Mark Roufaiel; Drayson Graves; Peter Pelka; Darwyn Kobasa; Roger DuMoulin-White; Arkady Mandel (Heliyon, 2024)
The anti-viral properties of a small (≈1 kDa), novel Ru(II) photo dynamic compound (PDC), referred to as TLD-1433 (Ruvidar™), are presented. TLD-1433 had previously been demonstrated to exert strong anti-bacterial and anti-cancer properties. We evaluated the capacity of TLD-1433 to inactivate several human pathogenic viruses. TLD-1433 that was not photo-activated was capable of effectively inactivating 50 % of influenza H1N1 virus (ID50) at a concentration of 117 nM. After photo-activation, the ID50 was reduced to <10 nM. The dose of photo-activated TLD-1433 needed to reduce H1N1 infectivity >99 % (ID99) was approximately 170 nM. Similarly, the ID99 of photo-activated TLD-1433 was determined to range from about 20 to 120 nM for other tested enveloped viruses; specifically, a human coronavirus, herpes simplex virus, the poxvirus Vaccinia virus, and Zika virus. TLD-1433 also inactivated two tested non-enveloped viruses; specifically, adenovirus type 5 and mammalian orthoreovirus, but at considerably higher concentrations. Analyses of TLD-1433-treated membranes suggested that lipid peroxidation was a major contributor to enveloped virus inactivation. TLD-1433-mediated virus inactivation was temperature-dependent, with approximately 10-fold more efficient virucidal activity when viruses were treated at 37 °C than when treated at room temperature (∼22 °C). The presence of fetal bovine serum and virus solution turbidity reduced TLD-1433-mediated virucidal efficiency. Immunoblots of TLD-1433-treated human coronavirus indicated the treated spike protein remained particle-associated.